EVALUASI USER EXPERIENCE APLIKASI INDONESIA PUSTAKA NASIONAL (IPUSNAS) MENGGUNAKAN METODE HEART METRICS: EVALUATION OF THE USER EXPERIENCE OF THE INDONESIAN NATIONAL LIBRARY APPLICATION (IPUSNAS) USING THE HEART METRICS METHOD - Fa'iqoh, Hanifatul; Suyatno, Dwi Fatrianto (Universitas Negeri Surabaya, 2024)
User experience is one of the important factors related to the success of a mobile application. If the user experience of an application is getting better, then users will feel satisfied and their loyalty will be higher. This study aims to (1) Measure the user experience of the iPusnas application using the HEART variable, (2) Know what needs to be improved based on the user experience of iPusnas application users, (3) Know the effect of Intention to Reuse iPusnas application users from the HEART Metrics method. The data in this study were obtained by distributing questionnaires to one hundred iPusnas application users with the Bookworm and Socializer levels. Based on the results of the study, it was found that not all HEART Metrics variables achieved the Goals to be achieved, namely the Adoption variable. The results of interval PLS data analysis show that 18 indicators used are valid and 1 indicator is invalid, so the indicator is removed. In addition, the results of the inner model evaluation show an R-Square value of 0.776 and 0.764 for interval and score data. Hypothesis testing shows that the HEART latent variable has a significant effect on Intention to Reuse. However, 2 insignificant variables need to be prioritized for improvement in user experience, namely Adoption and Retention.